Lithium ion battery negative electrode and preparation method and application thereof

By using a binder containing sulfide bonds in the negative electrode of the lithium-ion battery, the co-embedding of solvent molecules is prevented and the rapid diffusion of lithium ions is promoted, the problem of lithium dendrites is solved, and the circulation performance and safety of the battery are improved.

CN119069707BActive Publication Date: 2025-04-01CHANGSHA XINXING NEW ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411303770.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-04-01
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode materials are prone to form lithium dendrites during high-rate charging and discharging, resulting in unstable battery performance, high safety risks, and complex preparation methods for suppressing dendrites.

Method used

The negative electrode of the lithium-ion battery is adopted, which includes graphite powder and a specific binder. The binder consists of a copolymer of 1,1-difluoroethylene and Compound 1. Compound 1 contains sulfide ether bonds, which can prevent the co-embedding of solvent molecules and promote the rapid diffusion of lithium ions.

Benefits of technology

It effectively inhibits the growth of lithium dendrites, improves the circulation performance and safety of lithium-ion batteries, and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119069707B_ABST
    Figure CN119069707B_ABST
Patent Text Reader

Abstract

The present invention provides a negative electrode for a lithium ion battery, comprising graphite powder and a binder; the binder accounts for 1-3wt% of the graphite powder; the binder comprises a copolymer of 1,1-difluoroethylene and a sulfur-containing compound; wherein the weight ratio of 1,1-difluoroethylene to compound 1 is 100:1-3. The present invention also provides a preparation method and application of the negative electrode for a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion batteries, and in particular relates to a lithium ion battery negative electrode and a preparation method and application thereof. Background Art

[0002] In recent years, lithium secondary batteries have been widely used in many fields such as mobile electronic devices and new energy vehicles due to their excellent performance. The development of the new energy industry has also put forward higher requirements on the performance of lithium-ion batteries.

[0003] Graphite is the most widely used negative electrode material for lithium-ion batteries. Graphite has excellent electrical conductivity, so the diffusion behavior of lithium ions inside the graphite in the graphite negative electrode directly affects the performance of the battery. In theory, the lamellar structure of graphite is very conducive to the rapid transmission of lithium ions between the lamellar layers and exhibits excellent rate performance, but the actual situation is that the rate performance of pure graphite negative electrodes is poor. Large current charging and discharging can easily cause lithium ions on the surface of graphite to partially deposit due to lack of time to diffuse, forming lithium dendrites. In essence, the generation of lithium dendrites is mainly due to the uneven deposition of lithium ions on the electrode surface, which leads to the rapid deposition of lithium at the active points of the electrode. As the number of battery cycles increases, the degree of lithium deposition gradually increases. Under certain conditions, the deposited lithium will form lithium dendrites in a directional manner, puncture the diaphragm, cause a short circuit inside the battery, and cause a safety accident.

[0004] Normally, Li is stored in graphite negative electrodes mainly in the form of interlayer embedding storage, graphite layer end surface storage, and graphite crystal surface storage, among which the main capacity contribution comes from interlayer embedding storage. During the lithium ion embedding reaction, the alkyl groups at the electrode / electrolyte interface will promote the co-embedding of solvent molecules and lithium ions, thereby causing the exfoliation of graphite sheets and the reduction of the material's cyclic stability. To avoid this phenomenon, oxidation, fluorination, and coating of the graphite surface are effective solutions. At present, most of the porous materials used in lithium dendrite inhibition have complex preparation methods and high costs. Finding porous materials with controllable pore structures, excellent electrochemical properties, simple synthesis methods, and low costs has become the key to inhibiting dendrite growth.

[0005] The Chinese invention patent application with publication number CN108258241A discloses a ZIF-8 zeolite imidazolate framework porous material. As a special template precursor carbon material with regular pore structure and high specific surface area, it has the advantages of simple synthesis process and good conductivity. The ZIF-8 porous carbon material with regular pore structure, high specific surface area and good physical properties is used as a modified material, and a lithium battery negative electrode is prepared by simple physical coating, which effectively inhibits the growth of lithium dendrites during battery charging and discharging, thereby improving the cycle performance of the lithium battery.

[0006] The Chinese invention patent application with publication number CN117766765A provides an application of a metal single atom material as a graphite negative electrode additive for lithium-ion batteries. The metal single atom (single atom manganese) material has a good adsorption effect on lithium, and can induce uniform deposition of lithium precipitated from the graphite negative electrode under extreme conditions such as low temperature and high rate, avoiding the formation of lithium dendrites, thereby enhancing battery safety and life. In addition, the metal single atom material has the characteristics of simple preparation process, low synthesis cost, and large-scale preparation.

[0007] The Chinese invention patent application with publication number CN115172666A discloses a double-layer composite graphite negative electrode and a preparation method thereof, wherein the double-layer composite graphite negative electrode comprises a composite layer and a graphite layer, wherein the composite layer comprises silver nanoparticles and graphite, and when the double-layer composite graphite negative electrode is applied to a lithium-ion battery with an N / P ratio of less than 1, the composite layer is located between the current collector and the graphite layer of the lithium-ion battery. The invention is a double-layer graphite electrode, and by utilizing the excellent nucleophilic effect of silver on lithium, it can induce uniform deposition and stripping of excess lithium ions in the composite graphite negative electrode composite layer during battery charging and discharging, and can effectively inhibit the growth of lithium dendrites on the surface of the graphite negative electrode in low N / P lithium-ion batteries, improve battery safety, extend battery cycle life, and improve battery quality and volume energy density. Summary of the invention

[0008] The first object of the present invention is to provide a lithium ion battery negative electrode with high stability and high rate performance.

[0009] The second object of the present invention is to provide a method for preparing the negative electrode of the lithium ion battery.

[0010] The third object of the present invention is to provide an application of the negative electrode of the lithium ion battery.

[0011] The present invention is achieved through the following technical solutions:

[0012] A lithium-ion battery negative electrode,

[0013] including graphite powder and a binder;

[0014] The binder accounts for 1-3wt% of the graphite powder;

[0015] The binder includes a copolymer of 1,1-difluoroethylene and compound 1;

[0016] Wherein, the weight ratio of 1,1-difluoroethylene to compound 1 is 100:1-3;

[0017] The structure of compound 1 is as follows:

[0018] ;

[0019] Among them, 3≤n≤7.

[0020] The D50 of the graphite powder is 1-10 μm.

[0021] The method for preparing the negative electrode of a lithium ion battery comprises the steps of mixing graphite powder and a binder in a first organic solvent, loading the mixture on the surface of a substrate and drying the mixture.

[0022] The preparation method of compound 1 comprises the following steps:

[0023] Maleic anhydride and mercaptobenzene are mixed and subjected to addition reaction to obtain ;

[0024] Will Reaction with water to obtain ;

[0025] Will and Mixing, and performing esterification reaction to obtain compound 1;

[0026] The compound 1 is mixed with 1,1-difluoroethylene, an initiator is added, and a polymerization reaction is carried out to obtain the binder.

[0027] The catalyst used in the addition reaction includes triethylamine;

[0028] The solvent used in the addition reaction includes tetrahydrofuran.

[0029] The dehydrating agent used in the esterification reaction includes DCC;

[0030] The catalyst used in the esterification reaction includes DMAP.

[0031] The initiator includes an azo compound;

[0032] The azo compound includes azobisisobutyronitrile.

[0033] The organic solvent used in the polymerization reaction includes toluene;

[0034] The substrate includes copper foil.

[0035] The application of the lithium ion battery negative electrode is used in preparing lithium ion batteries.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] In the negative electrode of the lithium ion battery provided by the present invention, the sulfide bond in the binder can prevent the co-embedding of solvent molecules and promote the rapid diffusion of lithium ions on the graphite surface. At the same time, the surface modification of the graphite negative electrode of the lithium ion battery can improve the stability and cycle performance of the graphite negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The micrograph of the negative electrode of the lithium-ion battery prepared in Example 6 after 1000 cycles is shown. It can be seen from the figure that no lithium dendrites are generated in the negative electrode material.

[0039] Figure 2 The micrograph of the negative electrode of the lithium-ion battery prepared in Comparative Example 2 after 1000 cycles is shown. From the figure, it can be seen that a large number of lithium dendrites are generated in the negative electrode material.

[0040] Figure 3 The cycle performance diagram of the lithium ion battery negative electrode prepared in Example 6 and Comparative Example 2 is shown. DETAILED DESCRIPTION

[0041] The present invention first provides a negative electrode for a lithium-ion battery, specifically, it includes graphite powder and a binder; wherein the binder is used to bind the graphite powder to obtain the negative electrode for the lithium-ion battery. More specifically, the amount of the binder added is 1-3wt% of the graphite powder. More specifically, the binder includes a copolymer of 1,1-difluoroethylene and compound 1; wherein the weight ratio of 1,1-difluoroethylene to compound 1 is 100:1-3; the structure of compound 1 is as follows:

[0042] ; Wherein, 3≤n≤7. The reason for copolymerizing 1,1-difluoroethylene with compound 1 is to introduce thioether. The presence of thioether can prevent solvent molecules and lithium ions from being co-embedded in graphite. The presence of benzene ring as a rigid group can improve the rigidity of the negative electrode obtained by bonding the graphite with the binder. The ester group is a chemical group that can enhance the interaction force between the binder and the adherend and improve the bonding strength by forming hydrogen bonds with polar groups on the surface of the adherend. The introduction of the ester group can improve the polarity and intermolecular force of the binder, so that the binder can better infiltrate the surface of the adherend and form a stronger bond. In addition, the ester group can also improve the chemical stability and heat resistance of the binder, further enhancing the durability and reliability of the binder.

[0043] Specifically, the D50 of the graphite powder is 10-20 μm.

[0044] The present invention also provides a method for preparing the negative electrode of a lithium ion battery, which comprises the steps of mixing graphite powder and a binder in a first organic solvent, loading the mixture on a substrate surface and drying the mixture. The first organic solvent may be a non-polar solvent such as toluene, and after drying, the binder can bind the graphite powder.

[0045] The present invention provides a method for preparing compound 1, comprising the following steps:

[0046] Maleic anhydride and mercaptobenzene are mixed and subjected to addition reaction to obtain ; The reaction can be carried out using a thiol-Michael addition reaction.

[0047] Then Reaction with water gives ;

[0048] Will and The mixture is mixed and subjected to an esterification reaction to obtain compound 1. The esterification reaction can be carried out by a Fischer esterification method using concentrated sulfuric acid as a catalyst and heating, or by a variety of other esterification reactions such as a Steglich esterification reaction.

[0049] Then, after the compound 1 is mixed with 1,1-difluoroethylene, an initiator is added and a polymerization reaction is carried out to obtain the binder; the polymerization reaction can be carried out in various polymerization modes such as free radical polymerization.

[0050] Specifically, when the mercapto-Michael addition reaction is used, the catalyst used includes triethylamine; and the solvent used includes tetrahydrofuran.

[0051] When the Steglich esterification reaction is used, the dehydrating agent used may be DCC; and the catalyst used may be DMAP.

[0052] The initiator used in free radical polymerization can be an azo compound; specifically, the azo compound is azobisisobutyronitrile. The organic solvent used in polymerization can be toluene;

[0053] When preparing the negative electrode, the substrate used may be copper foil.

[0054] The present invention also provides the application of the lithium ion battery negative electrode, which can be used to prepare lithium ion batteries.

[0055] The present invention is further described below in conjunction with specific embodiments.

[0056] Example 1

[0057] Preparation by Mercapto-Michael Addition Reaction

[0058] 1 mol of maleic anhydride and 350 mL of dichloromethane were mixed in a flask, and 0.75 mL of triethylamine was added dropwise while stirring. After mixing evenly, 1 mol of mercaptobenzene was added to the dichloromethane solution of maleic anhydride at 30°C and stirring was continued for 3 hours. The solvent was removed by rotary evaporation and then dried. The dried product was recrystallized with petroleum ether to obtain .

[0059] Example 2

[0060] To the prepared Example 1 Add water and dry to obtain .

[0061] Example 3

[0062] Preparation by Steglich esterification

[0063] In a 50 mL round-bottom flask, 1 mol , 2mol , 1.5 mol DCC and 0.5 mol DMAP, then under the protection of N2, add dichloromethane, react at room temperature for about 6 hours (TLC detection), after the reaction is completed, filter, wash the filter cake with petroleum ether, ethyl acetate and acetone in turn, and dry to obtain.

[0064] Example 4

[0065] Preparation by Steglich esterification

[0066] The difference from Example 3 is that the raw material is HO-(CH2)5-CH=CH2.

[0067] Example 5

[0068] Preparation by Steglich esterification

[0069] The difference from Example 3 is that the raw material is HO-(CH2)7-CH=CH2.

[0070] Example 6

[0071] Preparation of negative electrode binder for lithium-ion batteries

[0072] In a 20L vertical polymerization reactor, add 0.06kg of the compound prepared in Example 3 and 5kg of toluene. Close the reactor and replace it with nitrogen several times to remove the air until the oxygen content in the reactor is less than 10ppm. Add 6.0kg of 1,1-difluoroethylene and 0.5kg of azobisisobutyronitrile. Heat the reactor to 45°C, start stirring the reactor at a speed of 800r / min. After reacting for 6h, release the pressure in the reactor, collect the liquid, and finally dry it in a 95°C oven for 24h to obtain a negative electrode binder for lithium-ion batteries.

[0073] Example 7

[0074] Preparation of negative electrode binder for lithium-ion batteries

[0075] The difference from Example 6 is that 0.06 kg of the compound prepared in Example 4 and 5 kg of toluene are added.

[0076] Example 8

[0077] Preparation of negative electrode binder for lithium-ion batteries

[0078] The difference from Example 6 is that 0.06 kg of the compound prepared in Example 5 and 5 kg of toluene are added.

[0079] Example 9

[0080] Preparation of negative electrode

[0081] A first graphite material with a D50 of 1.9 microns and a second graphite material with a D50 of 3.4 microns were mixed in a mass ratio of 100:25, and placed in a ball mill for high-speed ball milling, wherein the ball-to-material ratio of the high-speed ball milling was 2.5:1, the rotation speed was 180 rpm, and the ball milling time was 10 hours to obtain an electrode material;

[0082] Toluene was added to the stirring kettle, and the binder prepared in Example 6 was added to the solvent and stirred evenly, and then the electrode material was added and stirred evenly to obtain a negative electrode slurry, wherein the ratio of the binder to the graphite powder was 1wt%;

[0083] The negative electrode slurry is coated on the surface of the copper foil with a coating thickness of 75 microns, and dried to obtain a graphite negative electrode.

[0084] Example 10

[0085] Preparation of negative electrode

[0086] The difference from Example 9 is that the adhesive used is prepared by Example 7.

[0087] Embodiment 11

[0088] Preparation of negative electrode

[0089] The difference from Example 9 is that the adhesive used is prepared by Example 8.

[0090] Comparative Example 1

[0091] In a 20L vertical polymerization reactor, add 5kg of toluene. Close the reactor and replace it with nitrogen several times to remove the air until the oxygen content in the reactor is less than 10ppm. Add 6.0kg of 1,1-difluoroethylene and 0.5kg of azobisisobutyronitrile. Heat the reactor to 45℃, start stirring the reactor at a speed of 800r / min. After reacting for 6h, release the pressure in the reactor, collect the liquid, and finally dry it in a 95℃ oven for 24h to obtain a negative electrode binder for lithium-ion batteries.

[0092] Comparative Example 2

[0093] A first graphite material with a D50 of 1.9 microns and a second graphite material with a D50 of 3.4 microns were mixed in a mass ratio of 100:25, and placed in a ball mill for high-speed ball milling, wherein the ball-to-material ratio of the high-speed ball milling was 2.5:1, the rotation speed was 180 rpm, and the ball milling time was 10 hours to obtain an electrode material;

[0094] Toluene was added to a stirring kettle, and the binder prepared in Comparative Example 1 was added to the solvent and stirred evenly, and then the electrode material was added and stirred evenly to obtain a negative electrode slurry, wherein the mass ratio of the electrode material to the binder was 100:4;

[0095] The negative electrode slurry is coated on the surface of the copper foil with a coating thickness of 75 microns, and dried to obtain a graphite negative electrode.

[0096] Example 12

[0097] Preparation of negative electrode binder for lithium-ion batteries

[0098] In a 20L vertical polymerization reactor, add 0.18kg of the compound prepared in Example 3 and 5kg of toluene. Close the reactor and replace it with nitrogen several times to remove the air until the oxygen content in the reactor is less than 10ppm. Add 6.0kg of 1,1-difluoroethylene and 0.5kg of azobisisobutyronitrile. Heat the reactor to 45°C, start stirring the reactor at a speed of 800r / min. After reacting for 6h, release the pressure in the reactor, collect the liquid, and finally dry it in a 95°C oven for 24h to obtain a negative electrode binder for lithium-ion batteries.

[0099] Embodiment 13

[0100] Preparation of negative electrode

[0101] A first graphite material with a D50 of 1.5 microns and a second graphite material with a D50 of 9.8 microns are mixed in a mass ratio of 100:25, and placed in a ball mill for high-speed ball milling. The ball-to-material ratio of the high-speed ball milling is 2.5:1, the rotation speed is 180 rpm, and the ball milling time is 10 hours to obtain an electrode material;

[0102] Toluene was added to the stirring kettle, and the binder prepared in Example 12 was added to the solvent and stirred evenly, and then the electrode material was added and stirred evenly to obtain a negative electrode slurry, wherein the ratio of the binder to the graphite powder was 3wt%;

[0103] The negative electrode slurry is coated on the surface of the copper foil with a coating thickness of 75 microns, and dried to obtain a graphite negative electrode.

[0104] Battery cycle capacity retention test

[0105] The graphite negative electrode and lithium sheet were used to form an experimental battery, which was charged and discharged 1000 times with a current of 2C, and the battery's cycle capacity retention rate after 1000 charge and discharge cycles was measured.

[0106] Among them, the cycle capacity retention rate of the battery prepared by the lithium ion battery negative electrode prepared by Example 6 is 84.55%. The cycle capacity retention rate of the battery prepared by the lithium ion battery negative electrode prepared by Example 7 is 83.70%. The cycle capacity retention rate of the battery prepared by the lithium ion battery negative electrode prepared by Example 8 is 84.68%. The cycle capacity retention rate of the battery prepared by the lithium ion battery negative electrode prepared by Comparative Example 2 is 76.40%. The cycle capacity retention rate of the battery prepared by the lithium ion battery negative electrode prepared by Example 13 is 88.40%.

[0107] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.

Claims

1. A negative electrode for a lithium ion battery, characterized in that: including graphite powder and a binder; The binder accounts for 1-3wt% of the graphite powder; The binder includes a copolymer of 1,1-difluoroethylene and compound 1; Wherein, the weight ratio of 1,1-difluoroethylene to compound 1 of the copolymer is 100:1-3; The structure of compound 1 is as follows: ; Among them, 3≤n≤7.

2. The lithium ion battery negative electrode according to claim 1, characterized in that: The D50 of the graphite powder is 1-10 μm.

3. The lithium ion battery negative electrode according to claim 1, characterized in that: The preparation method of compound 1 comprises the following steps: Maleic anhydride and mercaptobenzene are mixed and subjected to addition reaction to obtain ; Will Reaction with water to obtain ; Will and Mixing, and performing esterification reaction to obtain compound 1; The compound 1 is mixed with 1,1-difluoroethylene, an initiator is added, and a polymerization reaction is carried out to obtain the binder.

4. The negative electrode of a lithium-ion battery as claimed in claim 3, characterized in that: The catalyst used in the addition reaction includes triethylamine; The solvent used in the addition reaction includes tetrahydrofuran.

5. The lithium ion battery negative electrode as claimed in claim 3, characterized in that: The dehydrating agent used in the esterification reaction includes DCC; The catalyst used in the esterification reaction includes DMAP.

6. The negative electrode of a lithium ion battery as claimed in claim 3, characterized in that: The initiator includes an azo compound; The azo compound includes azobisisobutyronitrile.

7. The negative electrode of a lithium ion battery as claimed in claim 3, characterized in that: The organic solvent used in the polymerization reaction includes toluene.

8. The method for preparing a negative electrode for a lithium ion battery according to claim 1, wherein: The method comprises the steps of mixing graphite powder and a binder in a first organic solvent, loading the mixture on the surface of a substrate and drying the mixture.

9. The method for preparing a negative electrode for a lithium ion battery according to claim 8, characterized in that: The substrate includes copper foil.

10. The use of the negative electrode of a lithium ion battery as claimed in claim 1, characterized in that: Used in the preparation of lithium-ion batteries.

Citation Information

Patent Citations

  • Negative electrode of lithium battery for inhibiting growth of lithium dendrites with ZIF-8 porous carbon material

    CN108258241A

  • Double-layer composite graphite negative electrode and preparation method thereof

    CN115172666A

  • Application of metal monatomic material as lithium ion battery graphite negative electrode additive and lithium ion battery graphite negative electrode

    CN117766765A

  • Modified binder as well as preparation method and application thereof

    CN116904147A

  • Negative electrode for nonaqueous secondary battery, and nonaqueous secondary battery using it

    JP2000067871A